PROBLEMATIKA BODY SHAMMING PADA MEDIA SOSIAL DIKAITKAN DENGAN UNDANG UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK SEBAGAIMANA DIUBAH DENGAN UNDANG UNDANG NOMOR 19 TAHUN 2016 - Micael Jeriko Damanik; Prof.Dr.Syafrudin Kalo,SH,M.Hum; Dr.M.Ekaputra, S.H,M.Hum; Dr.Jelly Leviza,SH,M.Hum (JURNAL JUSTIQA, 2021)
Technological developments nowdays will make all information more easily andaccessible. This condition makes humans more easily influenced by advertisements todiscuss the assessment of the ideal body in society. The ideal body assessment causesmany individuals to experience a body shame. The emergence of cybercrime is caused bymistakes or errors in the use of information and communication technology.The existenceof cybercrime in Indonesia is regulated in the Indonesian Criminal Code (KUHP).Regulations can be used as a basis for a reference to body shamming are found in Article310, Article 311 and Article 315 of the Indonesian Criminal Code. However, the mostlegal basis for body shamming is Article 315 of the Indonesian Criminal Code. Body shamming behavior or physical mockery of others will make an impact to anyone.Ironically, the treatment of body shamming is more often done by the closest peoplewhether it's family, relatives, work colleagues or friends.The impact caused by bodyshamming allows psychological disturbance to the victims. Even encourage suicidalbehavior. Victims whose posture is less than ideal and are bullied will therefore becomeinsecure, afraid to leave the house and then do not want to socialize. This could indicatea suicide attempt. The body shamming crime is a complaint offense. However, in itshandling the police also used a mediation approach.